EVALUATION OF OCCUPATIONAL HEALTH AND SAFETY MANAGEMENT SYSTEM (OHSMS) IMPLEMENTATION AT PT XYZ - Pramono , DwiyosoPramono; Purwanto , Agustinus Hariadi Djoko; Nugroho , Rosalendro Eddy (International Journal of Social and Management Studies, 2023)
— PT XYZ is an oil and gas infrastructure management and supply service company that has a very high level of work-related accident risk in every work activity. The company has a history of high cases of LTI / lost time injury (death/disabled) and non-LTI (first aid/near miss/property damage) work-related accidents in 2016 – 2020 so that the company's OHS target of Zero Accident (LTI=0) is not achieved. This study aims to 1) determine the factors causing the high rate of work-related accidents; 2) figure out how to improve OHS performance; 3) figure out the OHS program recommendations. This research is qualitative research with an exploratory approach based on a case study of OHS aspects in the company. The population of this study was 2,960 people and 118 people were taken as a sample. This study uses the Fishbone Diagram, 5Whys, and 5W+1H analysis methods to find out the root causes of the high rate of work-related accidents. The results of this study indicate that the cause of work-related accidents with the highest percentage is the Manpower aspect (47.4%), followed by the Method aspect (22.7%), Material (13.7%), Machine (6.5%), Environment (5.8%), and Measure (3.9%). This research shows the implications for the Company that by taking corrective actions and following up on research recommendations, the number of work-related accidents can decrease significantly in the period 2020 – 2021. According to the data, after the corrective action is implemented, the number of work-related accidents decreased to LTI (1 case) and non-LTI (16 cases); the number of OHS non-conformance audit results is 55 findings; the number of OHS non-conformance in the previous period that had not been followed up is 6 findings; OHSMS Application Score reached 96.38%. It is because there are managerial implications that have a real impact on company management which previously had a Profit Oriented mindset that has changed into Safety Oriented in every implementation of the company's business activities